2016
DOI: 10.1002/jbmr.2990
|View full text |Cite
|
Sign up to set email alerts
|

LOX Fails to Substitute for RANKL in Osteoclastogenesis

Abstract: Osteoclasts are the exclusive bone-resorbing cells that have a central role in bone homeostasis as well as bone destruction in cancer and autoimmune disease. Both mouse and human genetic studies have clearly proven that receptor activator of NF-kB ligand (RANKL; encoded by the Tnfsf11 gene) and its receptor RANK are essential for osteoclastogenesis. Although there have been several reports on RANKL-independent osteoclastogenesis, previous studies have never provided in vivo evidence showing RANKL can be substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 20 publications
6
31
0
1
Order By: Relevance
“…Consistent with previous observations (Cox et al, 2015; Tsukasaki et al, 2017), rLOX-enhanced osteoclast formation increased the rate of bone resorption, stimulating the formation of resorption pits (Figure 4A). To further characterize the involvement of LOX in osteo- clastogenesis and investigate the effect of rLOX treatment in vivo, we injected rLOX into the periosteal regions of female mouse calvaria once daily for 10 days.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous observations (Cox et al, 2015; Tsukasaki et al, 2017), rLOX-enhanced osteoclast formation increased the rate of bone resorption, stimulating the formation of resorption pits (Figure 4A). To further characterize the involvement of LOX in osteo- clastogenesis and investigate the effect of rLOX treatment in vivo, we injected rLOX into the periosteal regions of female mouse calvaria once daily for 10 days.…”
Section: Resultssupporting
confidence: 93%
“…The osteoclastogenic function of LOX seems to be dependent on LOX-mediated collagen cross-linking, because the expression of LOX wild-type, but not LOX oxidase-dead mutant, in LOX-depleted cells restored CM-induced osteoclast differentiation rates. Notably, and consistent with recent studies (Cox et al, 2015; Tsukasaki et al, 2017), our investigation demonstrated that rLOX can recapitulate the osteoclastogenic properties in vitro and stimulate bone resorption in vivo. These findings underscore the importance of mH2A1.2 in the regulation of LOX expression and also suggest that accurate targeting of mH2A1.2 within the LOX gene locus may be vital for the control of breast cancer-induced osteoclastogenesis and its related physiological responses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recently, possible RANKL-independent osteoclastogenesis has been reported by combinations of IL-6 and IL-11 [68], and TNF-α and IL-6 [69], and by lysyl oxidase (LOX) [70]. However, several investigators indicate that there is no clear evidence of RANKL-independent osteoclastogenesis or factor that replaces RANKL [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the membrane-bound form functions more efficiently than the soluble form, but there was no clear in vivo data to support this difference. 3),43), 44) To address this question, we generated mice in which the cleavage site of RANKL was deleted. 39), 45) The mice had no detectable soluble form of RANKL but a normal level of membranebound RANKL.…”
Section: Which Cells Express Rankl?mentioning
confidence: 99%